Penyelesaian Hadis Mukhtalif tentang Sumber Ajaran Islam - Atiyatul Ulya (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
In the perspective of Ulum al-Hadith, conflicting hadiths must be resolved, either by compromising or by giving preference to find the stronger one in quality. It is assumed that the Prophet Muhammad, as the role model for the Muslim community, would not make statements that contradict each other without explanation. Such a situation could confuse Muslims who are trying to understand and follow his teachings. Therefore, research on these Conflicting Hadiths needs to be conducted, especially concerning the primary sources of Islamic teachings that serve as benchmarks for legal provisions in Islam. If so, the issue worth investigating is: How to resolve Conflicting Hadiths to reach an integrative solution.